The Influence of Experimental Video Media and Curiosity on the Understanding of Mechanical Concepts: A Quasi-Experimental Study in Senior High School Physics Learning - Dilan Ayunika (Contextual Natural Science Education Journal, 2025)
This study aims to examine the effects of experimental video media and curiosity on students’ conceptual understanding of mechanics. The rationale for this research stems from the persistently low level of students’ conceptual understanding in mechanics, which is largely attributed to conventional instructional practices and limited opportunities for direct experimental experience. Experimental video media are expected to facilitate the visualization and contextualization of abstract physics concepts, while curiosity functions as an intrinsic motivational factor that encourages active engagement in the learning process. This study employs a quasi-experimental approach with a 2 × 2 factorial design. The sample consists of two classes selected through purposive sampling, and the research instruments include a mechanics conceptual understanding test and a curiosity questionnaire. The findings are expected to demonstrate that both the use of experimental video media and students’ curiosity have a positive and significant effect on conceptual understanding of mechanics.